Preparation of (14)C-Labeled Sterigmatocystin in Liquid Media - Hsieh, Dennis P. H. (1975)
(14)C-labeled sterigmatocystin was prepared from surface cultures of Aspergillus versicolor A-18074 maintained in liquid media by multiple additions of [1-(14)C]acetate to the cultures. The highest yield of 7.75 mg/10 ml was found with a sucrose-asparagine-ammonium medium in which more than 3% of the radioactivity of the added [1-(14)C]acetate was recovered in the purified [ring-(14)C] sterigmatocystin. The method offers an easy way to prepare (14)C-labeled sterigmatocystin for studies of this mycotoxin.